Intrusion detection in wireless ad hoc networks. - Mishra, A. (IEEE Wireless communications)
Intrusion detection has, over the last few years, assumed paramount importance within the broad realm of network security, more so in the case of wireless ad hoc networks. These are networks that do not have an underlying infrastructure; the network topology is constantly changing. The inherently vulnerable characteristics of wireless ad hoc networks make them susceptible to attacks, and it may be too late before any counter action can take effect. Second, with so much advancement in hacking, if attackers try hard enough they will eventually succeed in infiltrating the system. This makes it important to constantly (or at least periodically) monitor what is taking place on a system and look for suspicious behavior. Intrusion detection systems (IDSs) do just that: monitor audit data, look for intrusions to the system, and initiate a proper response (e.g., email the systems administrator, start an automatic retaliation). As such, there is a need to complement traditional security mechanisms with efficient intrusion detection and response. In this article we present a survey on the work that has been done in the area of intrusion detection in mobile ad hoc networks.